PENGEMBANGAN DESAIN GANTUNGAN PAKAIAN INKLUSIF UNTUK MEMUDAHKAN AKTIVITAS MENJEMUR PAKAIAN - Amelia Angelika; Winta Adhitia Guspara; Christmastuti Nur (ATRIUM: Jurnal Arsitektur, 2018)
Title: Development of Inclusive Hanger Design to Facilitate Clothes Drying Activities Laundry activities, including drying are still recommended to be done by the elderly independently. However, the decline in the physical condition of the elderly, including a decrease in the balance of body position, cannot be avoided. In the observation at the GKJ Gondokusuman nursing home, the drying place is uses a rope on the roof or pole that is quite high from the reach of the elderly hand. When drying clothes, the elderly must stretch their arms and tiptoe because of the differences in height of the clothesline. This condition can increase the risk of accidents for the elderly who lose balance. This study aims to develop a product to dry the laundry and reduce the distance between the users with a high clothesline. This product development was using design research and product design. The research method was based in ergonomics knowledge through an inclusive design approach. The techniques used were behavioral observation, assessment of body activities, like Nordic Body Map (NBM) and Rapid Entire Body Assignment (REBA). The results of the NBM stated that the elderly experienced pain in the right side of the body, while the results of the REBA assessment showed a score of 10. This condition showed that the elderly posture while drying still had a high risk of injury. As the results of these studies, the product is designed with a function to hang laundry that make user's body position more balanced because there is no need to stretch arms and tiptoe too high. Users also easily put clothes on the hanger because there is a grip feature for both hands.